2021
DOI: 10.1002/ccd.30052
|View full text |Cite
|
Sign up to set email alerts
|

Impact of blood pressure on coronary perfusion and valvular hemodynamics after aortic valve replacement

Abstract: Objective: Our objective was to evaluate the impact of various blood pressures (BPs) on coronary perfusion and valvular hemodynamics following aortic valve replacement (AVR).Background: Lower systolic and diastolic (SBP/DBP) pressures from the recommended optimal target range of SBP < 120-130 mmHg and DBP < 80 mmHg after AVR have been independently associated with increased cardiovascular and all-cause mortality. Methods:The hemodynamic assessment of a 26 mm SAPIEN 3 transcatheter aortic valve (TAV), 29 mm Evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Average ECF was between 58.8 and 73.5 ml/min, which is the physiological range for the RCA to achieve 70% of 4% to 5% of the total cardiac output. 15 , 19 The ECF was set within these physiological limits at 130/80 mmHg by setting the resistance of the coronary circuit at the beginning of the experiment. Then, once the baseline coronary conditions have been achieved, the coronary circuit parameters are held fixed as the systemic BPs are varied to evaluate the sole impact of aortic BP on the resulting coronary flow.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Average ECF was between 58.8 and 73.5 ml/min, which is the physiological range for the RCA to achieve 70% of 4% to 5% of the total cardiac output. 15 , 19 The ECF was set within these physiological limits at 130/80 mmHg by setting the resistance of the coronary circuit at the beginning of the experiment. Then, once the baseline coronary conditions have been achieved, the coronary circuit parameters are held fixed as the systemic BPs are varied to evaluate the sole impact of aortic BP on the resulting coronary flow.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, 15 we experimentally assessed the effect of SBP and DBP independently on epicardial coronary flow (ECF) variation and valve hemodynamics. We found that ECF decreased below the physiological minimum when BPs were in the recommended range.…”
Section: Introductionmentioning
confidence: 99%